The electrochemical catalytic behavior of pyrogallol at an 8-hydroxyquinoline-aluminum complex modified carbon paste electrode and its detection in tomato1. Issue 17 (27th February 2015) - Bao, Amin; Xiao, Nan; Zhu, Yongchun; Xin, Shigang; Zhang, Hongbo
<x xml:space="preserve">Abstract</x> Tomato (Solanum lycopersicum) fruit is an excellent food for promoting human health and wellbeing due to its containing polyphenols as antioxidants.